SMOKING RELATED HEALTH CARE COSTS (Tufts Archival Research Center, 2007)
Report on smoking related health care costs in Rhode Island. Divides costs into direct health care costs, indirect mortality coses, morbidity costs, and years of potential life lost. Provides estimate for the total of smoking attributable costs.